Antimicrobial activity of Isothecium alopecuroides and potential effect of some climate elements on the activity of this bryophyte sample - Altuner, Ergi̇n Murat; Cetin, Barbaros (Kastamonu University, 2018)
Aim of study: This study aims to present how some climate elements can dramatically affect the antimicrobial activity of a plant by using Isothecium alopecuroides (Lam. ex Dubois) Isov., a bryophyte, as a plant sample to put forward some important environmental factors.Material and Methods: Two bryophyte samples, which were collected from two different locations, namely Aydın and Muğla. Chloroform, benzene, diethyl ether, ethyl alcohol, methyl alcohol, ethyl acetate, sdH2O and 0.5 M Tris-HCl buffer (pH: 8.0) were used as extraction solvents. The antimicrobial activity were tested against Bacillus subtilis, Candida albicans, Escherichia coli, Listeria monocytogenes, Salmonella enteretidis, Shigella flexneri, Staphylococcus aureus and Yersinia enterocolitica by disk diffusion, minimum inhibitory concentration test and minimum bactericidal/fungicial concentration tests. Meteorological data were obtained from the Turkish State Meteorological Service.Main results: As a result, it was observed that the bryophyte sample collected from Aydın was only active against B. subtilis with only its benzene extract, but the sample collected from Muğla was active against B. subtilis, S. aureus, E. coli and C. albicans with its different extracts at different ranges. Some climate elements were also found to be important in the activity of samples.Research highlights: It is concluded that in any study based on secondary metabolites, the time and the environmental conditions, where the plant samples are collected should be taken into account.
Keywords: 2. Zero hunger; 13. Climate action